Representing embodied expertise: anorexia and the celebrity athlete's lifestyle advice. Issue 3 (3rd July 2022) - Verriet, Jon
ABSTRACT: Celebrity athletes have become a popular source for advice on healthy living. However, little research exists on the changing representations of their interventions. This article analyses the case of Dutch top cyclist Leontien van Moorsel, whose celebrity status increased after a highly-publicised struggle with anorexia. By examining biographies, cookbooks, and radio and TV appearances, it traces Van Moorsel's celebrification and her transformation into an experience-based expert on lifestyle, and more specifically, eating disorders. It argues that, following her 'anorexic period', the cyclist's physical appearance was presented as proof of her embodied expertise on defeating anorexia. Simultaneously, through her TV appearances as a coach for girls engaged in self-starvation, Van Moorsel reveals a tension between her 'experience' and her 'expertise': her representation as a dispassionate expert on anorexia demanded that she actively distanced herself from her own life story. Hence, the case of Van Moorsel demonstrates the possible contradictions in representations of celebrity athletes' expertise. However, it also shows that it is likely that the social field of sport will continue to offer unique possibilities for presenting celebrity athletes as experts on healthy living.